Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1016/j.molliq.2017.04.037
|View full text |Cite
|
Sign up to set email alerts
|

Electro-magneto-hydrodynamic peristaltic pumping of couple stress biofluids through a complex wavy micro-channel

Abstract: Biomimetic propulsion mechanisms are increasingly being explored in engineering sciences. Peristalsis is one of the most efficient of these mechanisms and offers considerable promise in microscale fluidics. Electrokinetic peristalsis has recently also stimulated significant attention. Electrical and magnetic fields also offer an excellent mode for regulating flows. Motivated by novel applications in electro-conductive microchannel transport systems, the current article investigates analytically the electromagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 106 publications
(48 citation statements)
references
References 48 publications
(47 reference statements)
2
46
0
Order By: Relevance
“…The current work has considered the Stokes couple stress model and has been confined to electrically nonconducting flow in the absence of electrical or magnetic fields. Future studies will examine Eringen micropolar non‐Newtonian liquids and consider electrohydrodynamic and magnetohydrodynamic heat transfer for Sakiadis stretching sheet flows.…”
Section: Discussionmentioning
confidence: 99%
“…The current work has considered the Stokes couple stress model and has been confined to electrically nonconducting flow in the absence of electrical or magnetic fields. Future studies will examine Eringen micropolar non‐Newtonian liquids and consider electrohydrodynamic and magnetohydrodynamic heat transfer for Sakiadis stretching sheet flows.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies of clinical MHD physiological transport include Saygih et al (hydromagnetic retention systems in prosthodontics in prostheses on buccal mucosal blood flow, Nijm et al (magnetic resonance imaging procedures involving MHD blood flow potential monitoring) and Vallbona et al (magnetic pain therapy). Computational studies of magnetic biofluid dynamics include Mustapha et al (time‐dependent multistenosed arterial flow with a marker and cell code), Tripathi and Bég (unsteady peristaltic thermal hydromagnetic pumping in intestinal dynamics using Mathematica software), Kenjereš and Righolt (magnetic capturing of drug carriers in neurovascular transport), Ardahaie et al (numerical and analytical study of the fluid flow of blood containing nanoparticles in a porous media affected by the magnetic field), Rashidi et al (hemotological magnetic filtration simulation with a differential transform method) and Tripathi et al (electrokinetic and MHD peristaltic microfluidic device simulation). Several researcher have also considered combined heat transfer and fluid flow in industrial flow with MHD, porous medium and other effects which can be seen in Saryazdi et al…”
Section: Introductionmentioning
confidence: 99%
“…(magnetic capturing of drug carriers in neurovascular transport), Ardahaie et al 21 (numerical and analytical study of the fluid flow of blood containing nanoparticles in a porous media affected by the magnetic field), Rashidi et al 22 (hemotological magnetic filtration simulation with a differential transform method) and Tripathi et al 23 (electrokinetic and MHD peristaltic microfluidic device simulation). Several researcher have also considered combined heat transfer and fluid flow in industrial flow with MHD, porous medium and other effects which can be seen in Saryazdi et al [24][25][26][27][28][29][30][31][32] A key feature of many biological liquids which is intrinsic to their proper functionality is rheology.…”
mentioning
confidence: 99%
“…The exact solutions of eqs. (11)- (14) is obtained under boundary conditions (15)- (17). Equation (13) is used in eq.…”
Section: Analytical Solutionsmentioning
confidence: 99%
“…Extensive studies of MHD peristaltic flows have been communicated and have demonstrated the excellent regulation of bolus growth which is possible with the careful implementation of magnetic fields. Examples of such studies include Misra et al [16] for viscoelastic fluid in a channel with stretching walls and Tripathi et al [17] for Newtonian conducting fluids.…”
Section: Introductionmentioning
confidence: 99%